A critical review of play among children in the light of prophetic traditions - Abdul Rahman, Nur Faraheen; Wan Sulaiman, Wan Shahida; Mohd. Daud, Noor Amali (Penerbit USIM, Universiti Sains Islam Malaysia (USIM), 2018)
Introduction Recently primary school management has been experiencing the dilemma of a contracted period of recess time due to time constraint to fulfil the academic demands. However, little is known as to how beneficial this move is. It is also unclear if leisure time and play among children is encouraged from the Islamic point of view and if it correlates with children cognitive ability. Method Critical review on Prophetic traditions guiding leisure time and play among children and its relationship on children’s cognitive ability were employed. Thematic analysis was done to demonstrate the findings. Result Various types of leisure activities have been observed during the times of the Prophet. There were children leisure activities that the Prophet himself involved in, even encouraged others to join. Play could increase the cognitive ability of the children for various reasons. However, findings on time allocation appropriate for the play and leisure activity was mixed. Conclusion The importance of leisure and play activities extend beyond fun and socialization. In the light of prophetic guidance it is intended to achieve goodness in this world and the hereafter while it also has implications on children’s cognitive ability. Future research direction is also discussed.